Policy Strategy in an Effort to Increase the Economic Independence of the Community of Creative Economy Actors in Ngawi Regency - Khoyrul Anwar; Sumiati; Istiana Wijayanti Mala; Reni Sulistyawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Creative economy is a new economic concept that combines information and creativity that relies on ideas and knowledge from human resources as factors of production. Ngawi Regency has abundant creative economic potential and resources. This paper aims to formulate an academic policy strategy for local governments related to the development of the creative economy in Ngawi Regency which has implications for economic independence, by identifying the problems, obstacles and challenges faced. This research uses a qualitative approach. Based on the results of this study, it was found that the obstacles to the creative economy in Ngawi Regency include: (1) Lack of marketing field capabilities; (2) Weak capital and financial accessibility; (3) Low competence of creative economy actors; (4) Weak Copyright Protection or Legality Aspects; and (5) Supporting infrastructure for production, management and information technology is still weak. To overcome these problems, concrete policy steps are needed from the Ngawi Regency Government, including by: looking for alternative financing for the creative economy, increasing the capacity of creative economic actors, helping to do marketing with an emphasis on local brands and through social media, and the most important part for the development of the creative economy is the Intellectual Property Right aspect. The combination of these steps, if carried out properly, will be able to increase the development of the creative economy in Ngawi Regency